BORDER CROSSINGS: USE OF LINGUISTIC STUDIES ACROSS SUBJECT DISCIPLINES - Maya Khemlani David; Aliyyah Nuha Faiqah Azman Firdaus; Syed Abdul Manan (University of Kuningan, 2019)
Cross-disciplinary research, involving scholars of multiple disciplines, has attracted much attention from universities recently. This type of study extends beyond simple collaboration in integrating data, methodologies, perspectives and concepts and engages with real world problems, especially as global complexities have undermined the underlying ideology of countability and singularity of various disciplines founded on antiquated notions of territorialization. Since most disciplines are transferred through language and linguistics sciences like socio-linguistics, applied-linguistics and psycho-linguistics, an interrogation of received discourses on language study has direct and indirect impact on almost all the other disciplines and can be used to enhance language related studies in different ways. This paper shall define cross-disciplinary research and provide an overview of how applied linguistics and professional studies interrelate, focusing on the fact that research across disciplines must yield output that advances and benefits society, while allowing for complex and nuanced assessments allowed by the porous borders of different disciplines. This paper shares the kind of cross-disciplinary research which marries linguistics, languages and communication with other disciplines (for example, studies based on socio-linguistics and health, law, business or industry) to show how knowledge achieved from such research can result in trans-disciplinary recombination and expertise in other professional domains.